2014
DOI: 10.1097/ccm.0000000000000486
|View full text |Cite
|
Sign up to set email alerts
|

Substance P Mediates Reduced Pneumonia Rates After Traumatic Brain Injury

Abstract: Objectives Traumatic brain injury results in significant morbidity and mortality and is associated with infectious complications, particularly pneumonia. However, whether traumatic brain injury directly impacts the host response to pneumonia is unknown. The objective of this study was to determine the nature of the relationship between traumatic brain injury and the prevalence of pneumonia in trauma patients and investigate the mechanism of this relationship using a murine model of traumatic brain injury with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 48 publications
(59 reference statements)
0
40
1
Order By: Relevance
“…The current study also showed that specific blockade of substance P (SP) signaling decreased survival to a pulmonary pathogen only in mTBI mice, confirming the mechanism of the improved survival. 4 The significance of this work is highlighted further by a 2015 report showing that TBI patients had increased levels of SP. 8 The mechanism of improved survival occurs through enhanced phagocytic cell clearance of bacteria.…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…The current study also showed that specific blockade of substance P (SP) signaling decreased survival to a pulmonary pathogen only in mTBI mice, confirming the mechanism of the improved survival. 4 The significance of this work is highlighted further by a 2015 report showing that TBI patients had increased levels of SP. 8 The mechanism of improved survival occurs through enhanced phagocytic cell clearance of bacteria.…”
mentioning
confidence: 81%
“…3 In contrast to these studies showing that the neuroimmune axis decreases immune responses, our previous work documented that head trauma patients showed significantly reduced rates of pneumonia compared with blunt trauma patients. 4 A murine model of mild traumatic brain injury (mTBI) was able to reproduce these findings with enhanced resistance to bacterial pneumonia compared with sham injury mice. 4 mTBI mice showed improved survival, augmented pulmonary neutrophil recruitment, and reduced bacterial burdens compared with sham-injured mice.…”
mentioning
confidence: 99%
See 3 more Smart Citations